Head and Neck Cancer in Suriname: An Epidemiologic Review of Clinical and Pathologic Features of Patients Treated Between 2009 and 2021 - Sangeeta K. Bisheshar; Els T.M. Dams; Mikel Chan; Lorian Slagter-Menkema; Harie Basdew; Tineke van der Sluis; Rabia N. Mohamedradja-Taus; Dave P. Ameerali; Ralph A.E. Akrum; Surya Sheorajpanday; Robert Mehilal; Rachel S. van Leeuwaarde; et al. (JCO Global Oncology)
PURPOSEThis study investigates the incidence and clinicopathologic characteristics of head and neck cancer (HNC) in the Surinamese population, with an emphasis on the burden of human papillomavirus (HPV) and Epstein-Barr virus (EBV).METHODSHistologically confirmed HNC diagnosed between 2009 and 2021 were retrospectively collected from the Academic Hospital Paramaribo, the country's diagnostic pathology center. Additional clinical data were acquired from three other hospitals. Incidence rates were expressed as crude rates and age-adjusted World Standardized Rates per 100,000 population. Annual percentage changes (APCs) were calculated with Joinpoint regression software. HPV and EBV status were determined on pretreatment biopsies or resections of 263 patients from whom histopathologic material could be collected.RESULTSOf 364 patients, 279 (76.6%) were male. A substantial increase in HNC incidence was observed (2012-2019: annual percentage change 6.8%). Oral cavity carcinoma was most common in the Hindustani population, nasopharyngeal carcinoma (NPC) in the Maroon and Javanese populations, and laryngeal carcinoma (LC) in the Creole population. Patients with LC were more often smokers, whereas patients with oropharyngeal carcinoma (OPC) more often consumed alcohol. Most patients presented with advanced-stage disease at diagnosis (73.0%). Among 60 OPCs, 21 (35.0%) were HPV positive, and among 47 NPCs 43 (91.4%) were EBV positive.CONCLUSIONAn increase in HNC incidence in Suriname has been observed that appears to be unrelated to a rise in OPC and is likely due to better diagnostic modalities and increase in the number of ear, nose, and throat specialists. Ethnic and lifestyle differences are seen in HNC primary tumor sites. The high proportion of advanced-stage disease at diagnosis highlights the urgent need to raise disease awareness and prioritize early detection to improve survival outcomes.